Oxidation of the albumin thiol to sulfenic acid and its implications in the intravascular compartment - Turell,L. (2009)
Human serum albumin (HSA) is the most abundant protein in the intravascular compartment. It possesses a single thiol, Cys34, which constitutes ~80% of the total thiols in plasma. This thiol is able to scavenge plasma oxidants. A central intermediate in this potential antioxidant activity of human serum albumin is sulfenic acid (HSA-SOH). Work from our laboratories has demonstrated the formation of a relatively stable sulfenic acid in albumin through complementary spectrophotometric and mass spectrometric approaches. Recently, we have been able to obtain quantitative data that allowed us to measure the rate constants of sulfenic acid reactions with molecules of analytical and biological interest. Kinetic considerations led us to conclude that the most likely fate for sulfenic acid formed in the plasma environment is the reaction with low molecular weight thiols to form mixed disulfides, a reversible modification that is actually observed in ~25% of circulating albumin. Another possible fate for sulfenic acid is further oxidation to sulfinic and sulfonic acids. These irreversible modifications are also detected in the circulation. Oxidized forms of albumin are increased in different pathophysiological conditions and sulfenic acid lies in a mechanistic junction, relating oxidizing species to final thiol oxidation products.